2021
DOI: 10.1002/batt.202000288
|View full text |Cite
|
Sign up to set email alerts
|

What Can Text Mining Tell Us About Lithium‐Ion Battery Researchers’ Habits?

Abstract: Artificial Intelligence (AI) has the promise of providing a paradigm shift in battery R&D by significantly accelerating the discovery and optimization of materials, interfaces, phenomena, and processes. However, the efficiency of any AI approach ultimately relies on rapid access to high‐quality and interpretable large datasets. Scientific publications contain a tremendous wealth of relevant data and these can possibly, but not certainly, be used to develop reliable AI algorithms useful for battery R&D. To addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 69 publications
3
34
0
Order By: Relevance
“…In that respect, the battery field, when compared to other technologies such as photovoltaics or organic chemistry applied to pharmaceutics, suffers from a major disadvantage: the lack of standardization for cell assembly, testing protocols, data acquisition, and analysis. Hence, despite the enormous volume of scientific publications (more than 30000 currently [ 42 ] ) and internal reports on battery technologies, a scattering of results, when indeed sufficient information is provided for comparison, is widely observed for given chemistries. [ 42 ] This difficulty is not new, but can hardly be solved when cell format, cycling protocols, and consequent performance metrics differ for each battery chemistry and application.…”
Section: Electrochemical Characterizations Of Battery Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In that respect, the battery field, when compared to other technologies such as photovoltaics or organic chemistry applied to pharmaceutics, suffers from a major disadvantage: the lack of standardization for cell assembly, testing protocols, data acquisition, and analysis. Hence, despite the enormous volume of scientific publications (more than 30000 currently [ 42 ] ) and internal reports on battery technologies, a scattering of results, when indeed sufficient information is provided for comparison, is widely observed for given chemistries. [ 42 ] This difficulty is not new, but can hardly be solved when cell format, cycling protocols, and consequent performance metrics differ for each battery chemistry and application.…”
Section: Electrochemical Characterizations Of Battery Interfacesmentioning
confidence: 99%
“…Hence, despite the enormous volume of scientific publications (more than 30000 currently [ 42 ] ) and internal reports on battery technologies, a scattering of results, when indeed sufficient information is provided for comparison, is widely observed for given chemistries. [ 42 ] This difficulty is not new, but can hardly be solved when cell format, cycling protocols, and consequent performance metrics differ for each battery chemistry and application. Mature technologies such as alkaline primary batteries and MnO 2 electrode materials were developed via the standardization of cell formats, but more recent technologies, notably Li‐ion batteries, still do not benefit from the implementation of such similar standards.…”
Section: Electrochemical Characterizations Of Battery Interfacesmentioning
confidence: 99%
“…Indeed, such approaches have been successfully applied to the field of materials science [133,134]. However, El-Bousidy et al from our group [135] showed, through similar text mining techniques, that LIB research articles show a general lack of consistent reporting of electrode properties, such as thicknesses, porosities, loadings, electrolyte volumes or surface areas. This poses serious problems for the completeness of the reported data, which hampers the correct prediction of battery properties through ML models, and brings out yet another example of the reproducibility crisis common to various scientific disciplines [136].…”
Section: Opportunities For MLmentioning
confidence: 99%
“…There are many papers published on the subject; while they offer sage advice from recognized authorities, they aren't necessarily themselves solutions. [1][2][3][4] As a service to our authors, reviewers and readers, we introduced the Emerging PV Reports (Figure 1), a collaboration with the Helmholtz Institute Erlangen-Nuremberg for Renewable Energy, Germany. This initiative aims to accelerate the development of emerging PV materials towards market readiness and to improve the reproducibility and quality of the associated data.…”
Section: Dear Readermentioning
confidence: 99%